Effective properties of a new auxetic triangular lattice: an analytical approach - L. Cabras; M. Brun (Fracture and Structural Integrity)
In this article we propose a new auxetic periodic lattice with negative Poisson's ratio which tends to the limit ν=-1 under particular conditions. We have studied its generation and kinematic, and we give a full description of the mechanical properties of this innovative model. Calibrating the geometrical configuration of the lattice and the mechanical properties of the constituent material we are able to have a Poisson's ratio which is arbitrarily close to -1.